Menerapkan Teori Konseling Realitas sebagai Intervensi untuk Mengurangi Perilaku Bullying - Meiwati Harefa; Mondang Munthe; Hosianna Rodearni Damanik; Famahato Lase (Journal on Education, 2024)
Bullying behavior and victims, whether verbal, non-verbal or indirect, can be alleviated with the WDEP technique's reality counseling. The aim of this research is to apply reality counseling theory as an intervention to reduce bullying behavior in students using the one group pretest-posttest design experimental method, namely to determine the effects before and after treatment or O1 X O2. O1 is the pretest value. X is the reality treatment or counseling and O2 is the posttest value. The population of this study was all students in class IX of SMP Negeri 1 Gunungsitoli Utara and the sample was drawn using purposive sampling, totaling 30 people. Data was collected through initial and final test instruments and analyzed by comparing the results of O1 with O2 and then the results were described. The research results concluded that the WDEP reality counseling technique was very effective in alleviating the problem of bullying in students, both verbal, non-verbal and indirect bullying. This is evidenced by three students (10%) who carried out verbal bullying with the behavior of giving bad calls to their friends and making fun of them, 2 people (6.67%) who carried out non-verbal bullying against their friends such as spitting at them, showing ugly facial expressions and shouting. , two (2) people (6.67%) carried out indirect verbal bullying, namely carrying out behavior that excluded and silenced their friends and twenty-three (23) other people (76.67%) participated in bullying. Victims of bullying have also been able to overcome their problems, whether verbal, non-verbal or indirect bullying. This is evidenced by the decrease in the client's anxiety to zero level, they have a useful life plan, assess the behavioral plans they have made and the changes in behavior that have occurred to them as well as the client's processes and goals. It is recommended for school counselors to plan and implement WDEP technical reality counseling services to eradicate bullying behavior in students.